2017
DOI: 10.1038/s41598-017-09972-x
|View full text |Cite|
|
Sign up to set email alerts
|

Retrograde trafficking of β-dystroglycan from the plasma membrane to the nucleus

Abstract: β-Dystroglycan (β-DG) is a transmembrane protein with critical roles in cell adhesion, cytoskeleton remodeling and nuclear architecture. This functional diversity is attributed to the ability of β-DG to target to, and conform specific protein assemblies at the plasma membrane (PM) and nuclear envelope (NE). Although a classical NLS and importin α/β mediated nuclear import pathway has already been described for β-DG, the intracellular trafficking route by which β-DG reaches the nucleus is unknown. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 49 publications
(69 reference statements)
0
25
0
Order By: Relevance
“…A recent study in prostate cancer cells showed cell densitydependent γ-secretase and furin-mediated proteolysis of β-dystroglycan which could be stimulated by Notch, leading to nuclear targeting [111]. Another work uncovered the mechanism of retrograde trafficking of βdystroglycan from the plasma membrane to the nucleus [112]. In immortalized mouse C2C12 myoblasts, after being synthesized in the ER, α-Dg and β-Dg are transported from the ER to the Golgi apparatus and then to the plasma membrane, to form the DGC.…”
Section: Nuclear Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in prostate cancer cells showed cell densitydependent γ-secretase and furin-mediated proteolysis of β-dystroglycan which could be stimulated by Notch, leading to nuclear targeting [111]. Another work uncovered the mechanism of retrograde trafficking of βdystroglycan from the plasma membrane to the nucleus [112]. In immortalized mouse C2C12 myoblasts, after being synthesized in the ER, α-Dg and β-Dg are transported from the ER to the Golgi apparatus and then to the plasma membrane, to form the DGC.…”
Section: Nuclear Proteinsmentioning
confidence: 99%
“…In immortalized mouse C2C12 myoblasts, after being synthesized in the ER, α-Dg and β-Dg are transported from the ER to the Golgi apparatus and then to the plasma membrane, to form the DGC. The phosphorylation on β-Dg on Tyr890 causes its endocytosis from the plasma membrane and retrograde intracellular trafficking to the ER and then to the nucleus, mediated by β-Dg interaction with the Sec61 translocon complex [112].…”
Section: Nuclear Proteinsmentioning
confidence: 99%
“…Although dystroglycans are usually detected in the cell membrane, a nuclear localization signaling (NLS) sequence has been identified in β-Dystroglycan (Lara-Chacón et al, 2010). There is also report that dystroglycans can be translocated to the nuclear membrane in C2C12 myoblast cell lines, playing an important role in maintaining the integrity of the nuclear envelope (Gracida-Jiménez et al, 2017;Velez Aguirela et al, 2018). Our results suggest that agrin regulates epicardial EMT through aggregation of dystroglycans.…”
Section: Agrin Promotes Emt Through Aggregation Of Dystroglycanmentioning
confidence: 98%
“…To reach the NE, β-DG undergoes retrograde trafficking from the cell surface to the nucleus, via the membranous endosome-endoplasmic reticulum (ER) route. Exit of β-DG from the ER membranous environment is facilitated by the Sec61 translocon complex [ 8 ] and nuclear translocation is completed through recognition of the β-DG nuclear localization signal by importins α2/β1 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within the nucleus β-DG forms a complex with the NE proteins emerin and lamins A/C and B1, to preserve nuclear structure and function [ 4 , 10 ] and probably to regulate gene expression [ 11 ]. It is possible that nuclear trafficking of β-DG connects functionally the plasma membrane with the NE, via an as yet undefined mechanism, thus allowing the cell to orchestrate nuclear activity in response to external stimuli [ 8 ]. A better characterization of the interaction between of β-DG and its NE interacting partners will help to decipher the molecular basis underlying its role in critical nuclear processes.…”
Section: Introductionmentioning
confidence: 99%